TOURIST OR EXPLORER? DELVING STUDENTS’ PREDILECTION AND ANXIETY IN SEMANTICS COURSE - Sagala, Rakhmat Wahyudin; Rezeki, Tri Indah (EXPOSURE : JURNAL PENDIDIKAN BAHASA INGGRIS, 2024)
Within this particular study, the designations of "Tourist" and "Explorer" are employed to denote students who approach their classroom learning experiences with either a desire for leisurely exploration (akin to that of a tourist) or a desire to delve deeper into the subject matter (more akin to that of an explorer). The semantics course delves deeply into the theory of meaning, fields of meaning, and sense, and specific topics within the course material may cause some anxiety for students. The objective of this research is to explore how anxiety affects the acquisition of knowledge in semantics courses, given that anxiety can have an adverse impact on mental well-being. This research uses a survey design, adopting Spielberger's State-Trait Anxiety Inventory (STAI) as the instrument. Forty-six individuals voluntarily completed a questionnaire regarding their learning experience. The respondents aged between 20 and 24 years old. There were 15 male individuals in the group, representing 32% of the total, while 31 female individuals comprised 67% of the group. In order to enhance the overall effectiveness of educational achievements, forthcoming studies will be taking into account supplementary factors. Through the lens of "Tourist or Explorer? Delving Students' Predilection and Anxiety in Semantics Course," this study advances our comprehension of the multifaceted nature of semantics education, inviting a more empathetic and comprehensive approach to pedagogy.